Optimizing Corporate Social Responsibility (CSR) for Enhancing Economic Resilience in Coastal Communities: An Inclusive Development Model - Mareta, Sigit; Meiwanto Doktoralina, Caturida; Lestari, Lestari (Dinasti International Journal of Economics, Finance & Accounting, 2024)
In the context of sustainable development, the role of corporate social responsibility has gained significant importance, particularly in resource-based industries operating in coastal regions. This research paper proposes an inclusive development model that integrates ethical values and community engagement to foster economic resilience and environmental sustainability in coastal communities. Coastal communities often face unique socioeconomic and environmental challenges owing to their heavy dependence on natural resources, heightened vulnerability to the impacts of climate change, and the complex interplay between economic activities and fragile ecosystems. (Bhale & Bh?le, 2017) The global economic slowdown has significantly affected coastal communities, particularly in regions heavily reliant on the maritime sector. This study explores how Corporate Social Responsibility (CSR) can be utilized to enhance economic resilience, focusing on empowering women and fostering social inclusion in these communities. Utilizing both quantitative and qualitative research methods, including literature reviews, interviews, and field observations, this study aims to develop an inclusive CSR model integrated with accounting principles. Findings indicate that structured CSR initiatives have a positive impact on local economies, particularly when tailored to address specific community needs. This study contributes to the existing literature by providing a practical framework for businesses to implement sustainable CSR strategies that benefit coastal communities